Social Cooperation and Disharmony in Communities Mediated through Common Pool Resource Exploitation - Sugiarto, Hendrik Santoso (2017)
It was theorized that when a society exploits a shared resource, the system can undergo extreme phase transition from full cooperation in abiding by a social agreement, to full defection from it. This was shown to happen in an integrated society with complex social relationships. However, real-world agents tend to segregate into communities whose interactions contain features of the associated community structure. We found that such social segregation softens the abrupt extreme transition through the emergence of multiple intermediate phases composed of communities of cooperators and defectors. Phase transitions thus now occur through these intermediate phases which avert the instantaneous collapse of social cooperation within a society. While this is beneficial to society, it nonetheless costs society in two ways. First, the return to full cooperation from full defection at the phase transition is no longer immediate. Community linkages have rendered greater societal inertia such that the switch back is now typically stepwise rather than a single change. Second, there is a drastic increase in social disharmony within the society due to the greater tension in the relationship between segregated communities of defectors and cooperators. Intriguingly, these results on multiple phases with its associated phenomenon of social disharmony are found to characterize the level of cooperation within a society of Balinese farmers who exploit water for rice production.